Efeitos do fentanil, droperidol e inoval sobre função renal e eletrólitos (sódio e potássio) - Braz, José Reinaldo Cerqueira [UNESP]; Vianna, Pedro Thadeu Galvão [UNESP]; Hossne, W. S. (My University, 1976)
The influence of Fentanyl, Droperidol and Innovar on renal function and electrolytes (sodium and potassium) were studied on 18 dogs. Fentanyl disturbs kidney function and decreases plasmatic potassium. Droperidol and Innovar do not disturb the main renal function but decrease plasmatic potassium. The results obtained point out the importance of associate employment of Fentamyl and Droperidol, since the latter seems to establish the renal disorders occasioned by Fentanyl, probably owing to its adrenergic α blocking action.
Effects of fentanyl, droperidol and Innovar on renal function and electrolytes (sodium and potassium). Experimental study in the dog
Keywords: droperidol; droperidol plus fentanyl; fentanyl; dog; hyperkalemia; kidney function; neuroleptanalgesia; potassium blood level; theoretical study